Pengaruh Penyuluhan Menggunakan Video (VINEMA) terhadap Tingkat Pengetahuan Ibu Hamil dengan Anemia - Salwa Annisaa; Nurhayani Nurhayani (Universitas Muhammadiyah Manado, 2026)
Background: Anemia among expectant mothers persists as a critical public health concern, posing significant risks to both maternal and fetal well-being. National data indicates a prevalence of 48.9% in Indonesia; notably, Central Java remains a focal point for this issue, recording some of the highest statistics in the country. Effective education is essential to prevent anemia, and animated video media is considered more engaging and easier for pregnant women to understand. Objective: To determine the effect of counseling using educational videos on the knowledge of pregnant women with anemia. Methods: This study used a a quasi-experimental pretest–posttest design involving 44 pregnant women diagnosed with anemia, who were assigned to either an experimental or a control group. Statistical analysis was conducted using the Mann–Whitney test. Findings revealed an improvement in the average knowledge score from 8.91 at baseline to 9.23 following the intervention, with a significant mean difference of 1.18 recorded in the post-intervention phase. However, counseling using video did not significantly affect knowledge (p>0.05). Conclusion: Counseling using video media (VINEMA) did not yield a statistically significant improvement in the knowledge levels of pregnant women suffering from anemia. Nevertheless, this medium shows potential as a supplementary educational resource for fostering favorable attitudes regarding the prevention of anemia.